Prednisolone is associated with a worse lipid profile than hydrocortisone in patients with adrenal insufficiency - Marcus Quinkler; Bertil Ekman; Claudio Marelli; Sharif Uddin; Pierre Zelissen; Robert D Murray (Endocrine Connections, 2016)
Objective: Prednisolone is used as glucocorticoid replacement therapy for adrenal insufficiency (AI). Recent data indicate that its use in AI is associated with low bone mineral density. Data on risk factors for cardiovascular disease in patients with AI treated with prednisolone are scarce, despite this condition being the predominant cause of excess mortality. We aimed to address this question using real-world data from the European Adrenal Insufficiency Registry (EU-AIR). Design/methods: EU-AIR, comprising of 19 centres across Germany, the Netherlands, Sweden and the UK, commenced enrolling patients with AI in August 2012. Patients receiving prednisolone (3–6 mg/day, n = 50) or hydrocortisone (15–30 mg/day, n = 909) were identified and grouped at a ratio of 1:3 (prednisolone:hydrocortisone) by matching for gender, age, duration and type of disease. Data from baseline and follow-up visits were analysed. Data from patients with congenital adrenal hyperplasia were excluded. Results: Significantly higher mean ± s.d. total (6.3 ± 1.6 vs 5.4 ± 1.1 mmol/L; P = 0.003) and low-density lipoprotein (LDL) cholesterol levels (3.9 ± 1.4 vs 3.2 ± 1.0 mmol/L; P = 0.013) were identified in 47 patients on prednisolone vs 141 receiving hydrocortisone at baseline and at follow-up (P = 0.005 and P = 0.006, respectively). HbA1c, high-density lipoprotein and triglyceride levels, body mass index, systolic and diastolic blood pressure and waist circumference were not significantly different. Conclusions: This is the first matched analysis of its kind. Significantly higher LDL levels in patients receiving prednisolone relative to hydrocortisone could predict a higher relative risk of cardiovascular disease in the former group.